Dhaif Ma'mul Hadith Category in the Constellation of Hadith Sciences - Maya Veronica; Muhlas Muhlas (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith dhaif ma'mul according to the science of hadith. This research is a qualitative type by applying a literature study to interpret the hadith of dhaif ma'mul according to the science of hadith with a content analysis approach. The results of this discussion include the understanding of dhaif hadith, kinds of dhaif hadith and how dhaif ma'mul hadiths. This study concludes that there are many kinds of dhaif Hadith, all of which cannot be denied. There are dhaif hadiths that can be practiced, such as dhaif hadiths caused by the breaking of the chain, or due to majhul, and others where kedhaifan has been categorized in that category